PARKING MANAGEMENT SYSTEM USING ARDUINO (International Journal of Food and Nutritional Sciences, 2023)
With continuous growth in the population, therehas been an increase in personal and publicvehicles. Easy transportation is a basic need intoday‟s world where time is most precious.